The Role of Local Wisdom as Social Capital of Remote Indigenous Communities (RIC) - Dewinta Rizky R. Hatu; Darsono Wisadhirana; Edi Susilo (Universitas Muhammadiyah Jember, 2019)
This research sees that every community has local wisdom which is a source of social capital that can be accessed and utilized by its members. In this case, the community by itself builds their own social capital, with relationships built between communities through the local wisdom. The traditional remote community, certainly not separated from potential conflicts, but they can always overcome the potential conflicts that exist between them, because the role of local wisdom as a strong social capital among them. The theory used on this research is social capital Putnam and conducted in Buhu Village, Tibawa District, Gorontalo County, Indonesia. This research utilized case study as qualitative approach. Data collecting used in-depth interview, observation and documentation. Data were collected from six informants by using snowball sampling technique. This research found that the element of solidarity is important in building a strong social capital in the traditional remove community. This is different from Putnam which only emphasizes three elements, beliefs, networks and norms. In addition, the researchers found that in the process of networking, the traditional remote community is not only dealing with people they know, they are also different with Putnam as to realize various things, often people ask for help from their friends, family or trusted acquaintance (Field, 2010, hal. 3). The ‘huyula’ local wisdom that builds the social capital in the traditional remote community is able to bridge the differences that exist in a community, and can overcome the potential conflicts in the traditional remote community.